The Voodoo Ethnologists of Omega. Issue 3 (2nd July 2020) - Gordon, Rob
ABSTRACT: South Africa's colony, Namibia, served as a crucial testing ground for apartheid: not only was it the scene of the only significant effort to impose 'grand apartheid', but also of its demise. This essay examines the role of social engineering experts in these efforts by focusing on their role in the social construction of Omega base which housed Bushman soldiers. Treating Omega as an extended case study, I trace out the impact of these decisions and how they helped fashion mechanisms of contra-mobilisation used in the internal pacification of anti-apartheid groups like the UDF. The modus operandi of these experts favoured conspiracy theories and their methodology was akin to acts of divination. I argue that they constituted a 'Potted Factory' in three important ways: Firstly, potted refers to the way facts and ideas were summarised, abbreviated and decontextualised and became part of the symbolic currency of exchange; secondly, they were enclosed ideologically in a closed system or a sealed container; thirdly, 'potted' refers to being high, which they were in a figurative sense. Of course, my own analysis also makes use of conspiracy theories as I attempt to explore the 'dark side' of military intelligence.